Phosphorylcholine intranasal immunization with a 13-valent pneumococcal conjugate vaccine can boost immune response against Streptococcus pneumoniae. Issue 3 (16th January 2020) - Ohori, Junichiro; Iuchi, Hiroyuki; Maseda, Yoshiko; Kurono, Yuichi
Highlights: Effects of PCV13 vaccination and intranasal (IN) immunization were assessed in mice. PCV13 followed by phosphorylcholine boosted immune response against S. pneumoniae. IN can achieve protection against S. pneumoniae serotypes not contained in PCV13. Abstract: Objective: This study aimed to investigate whether systemic immunization with a 13-valent pneumococcal conjugate vaccine (PCV13) followed by intranasal (IN) immunization with phosphorylcholine (PC) can boost immune response against Streptococcus pneumoniae . Materials and methods: Two weeks after the intraperitoneal (IP) injection of PCV13, mice were divided into two groups (mice requiring another IP injection of PCV13 and mice requiring PC-keyhole limpet hemocyanin IN immunization in combination with cholera toxin as a mucosal adjuvant) to compare the magnitude of systemic and mucosal immune responses against S. pneumoniae and PC. Results: Serum immunoglobulin (Ig) G antibody titer against the vaccine strains of S. pneumoniae was similar between the PCV13 systemic immunization group and PC IN immunization group, while the serum IgG antibody titer against PC was significantly higher in the PC IN immunization group. PC-specific IgA antibody titer in the nasal lavage and PC-specific IgA-producing cell number in the nasal mucosa were also significantly higher in the PC IN immunization group. Induction of PC-specific IgA in the PC IN immunization group enhanced the clearance of bacteria from the middle ear. Conclusion: Additional IN immunization with PC after PCV13 immunization, which is currently conducted under a periodic vaccination program, can produce a booster effect comparable to that achieved by additional systemic immunization as well as PC-specific mucosal immune response, thereby providing protection against S. pneumoniae serotypes not contained in PCV13.